Study of the suffixes in the Huarochiri Manuscript (16th century) - Baldoceda Espinoza, Ana (2019)
Gerald Taylor, the renowned specialist in the Huarochiri Manuscript (HM), translated the Quechua text and provided a phonological writing, but a grammar analysis or a description of suffixes was beyond the scope of his work, so we set about analysing the suffixes. This article is based upon research carried out in the project «Estudio de los sufijos del Manuscrito Quechua de Huarochiri (s. XVI)» (‘Study of the suffixes in the Huarochiri Manuscript (16th century)’) in which we analyzed the suffixes used in the Huarochiri Manuscript (HM), both those of the noun and verb paradigms as well as the enclitic ones. In the noun paradigm the features of formative suffixes have been described, which helps to know the «cloaked» root of words ending in -n and -y, like hatun wakin, uray. In the verb paradigm the presence of suffixes such as -mpu and -tamu has been recorded (these suffixes are no longer used in modern varieties of Quechua). It has also been established that the presence of the suffixes -mu and -pu has no effect on -ku; so, in the HM we find ruraykupuy, no ruraykapuy.